The End of Welfare as We Know It? Continuity and Change in Western Welfare State Settings and Practices - Sandermann, Philipp (Verlag Barbara Budrich, 2014)
During the last 30 years, the governments of many Western countries have repeatedly called for an end to welfare. While the virtue of this goal and the means of achieving it continue to be debated in politics, much of contemporary social science research assumes that, in fact, the end of the welfare state has already occurred. The authors of this volume hope to contribute to a clearer understanding of how, where and to what extent welfare state settings really have changed since the 1980s. Their work examines questions of change and continuity while exploring various welfare practices in the Western world.